Determinants influencing performance of employees in public organizations: The case of Ho Chi Minh City - Ngo Hoai Son; Pham Thao Vy (Masyarakat, Kebudayaan dan Politik, 2022)
Ho Chi Minh City is a socioeconomic center in Vietnam with more than 122,111 public employees estimated in 2020. With the purpose of increasing performance of public servants, the research concentrates on public employees' perception of factors affecting their performance in the public sector in this city. From April 1st to April 30th, 331 survey forms were delivered to the low and middle public employees by two ways including 251 online and 80 offline surveys. Only 256 questionnaires were considered appropriate for analysis. The research used a quantitative approach and utilized descriptive statistics, reliability analysis, EFA, Pearson correlation analysis, and multiple linear regression via SPSS version 20. This study show that there is a statistically significant (0.05) relationship between the factors of recruitment and selection process, leadership, organizational culture, and reward management have a statistically significant impact on employee performance while there was no evidence to depict any association between working environment, training and development, and employee performance (p > 0.05). This study concludes that more attention and readjustment to reward management factors, organizational culture, recruitment and selection processes, and leadership are able to improve employee performance in public organizations.